Automating a Web-based Employee Management Information System using Agile Scrum - Putra, Rafi Risqullah; Maria (SCOPUS ID: 57093633500), Evi (Sistemasi: Jurnal Sistem Informasi, 2025)
Effective employee management is a critical factor in enhancing operational efficiency and organizational competitiveness. PT Sekawan Sahabat Sejati has faced challenges in employee administration due to manual processes using Microsoft Excel. These challenges include payroll calculation errors, difficulty in tracking data revisions, and delays in salary processing. This study aims to design and implement a web-based employee management information system to address these issues. The Agile Scrum methodology was employed, with data collected through field observations, stakeholder interviews, and literature reviews. The system was designed using an Entity Relationship Diagram and developed with the Next.js framework, TypeScript, and PostgreSQL as the database. The results show that the system can accurately automate base salary, allowances, and tax deductions, significantly reducing manual errors and accelerating the payroll process. System testing demonstrated notable improvements: payroll report generation time was reduced from 15 minutes to 4.02 seconds, attendance processing from 2 minutes to 3.08 seconds, creation of 500 employee records from 60 seconds to 1.2 seconds, and shift configuration storage from 3 minutes to 0.81 seconds. The application has proven to enhance administrative tasks by making them more efficient, transparent, and accountable. For future development, it is recommended to add mobile features, conduct user acceptance testing, and strengthen security through multi-factor authentication.